Emerging Concepts and Evidence in Telematics Novel Approaches or Treatments for Spasticity Management After Botulinum Injection - Helena Bascuñana-Ambrós; Mª Josep Nadal-Castells; Eliot Ramírez-Mirabal; Marta Beranuy-Rodriguez; Alberto Pintor-Ojeda; Jean-Claude (Frontiers Media S.A., 2021)
There is a strong recommendation for the use of intramuscular botulinum toxin in patients with persistent or progressive spasticity affecting one or more joints and who have an identifiable therapeutic target. After a botulinum toxin injection, a stretching intervention improves the results of the treatment, and it should be performed by patients and/or caregivers after being trained by a therapist. Adherence to this recommendation remains low once the therapist stops following the patient. The COVID-19 pandemic has increased the use of telemedicine with different approaches to treat patients. There has been an increased use of motivational applications, with virtual reality software and real-life videos, which provide a gaming experience that increases adherence. There are programs with synchronous telehealth exercises guided by physical therapists or software with sensor-based technology that shows the range of motion (ROM) and strength of the muscles of a particular joint. These new approaches to patient follow-up appear to increase adherence to exercise because they need to be "watched and controlled" is achieved.